Hubungan Faktor Kimia Udara (PM2.5, PM10) dan Kondisi Psikososial dengan Keluhan Sick Building Syndrome - Pramawati, Anita; Oktarizal, Hengky; Rarasati, Fauziah (Jurnal Kesehatan Komunitas, 2025)
Sick Building Syndrome (SBS) was a collection of symptoms associated with poor indoor air quality, with higher symptom severity among individuals experiencing psychosocial issues. This study aimed to determine the relationships between air chemical factors (PM2.5, PM10) and psychosocial conditions and sick building syndrome complaints. The research methodology used was quantitative with a cross-sectional study design. The sampling technique employed was total sampling, with a sample size of 41 individuals. Data analysis was conducted using the chi-square test at a 95% confidence level (α = 0.05). The results showed that 24 workers (58.5%) experienced SBS complaints. There was no significant association between CO and SBS complaints (p-value = 0). However, there was a significant correlation between PM2.5 (p-value = 0.031), PM10 (p-value = 0.031), and psychosocial conditions (p-value = 0.007) with SBS complaints. This study concluded that there was no significant correlation between CO and SBS complaints. However, a correlation was found between PM2.5, PM10, and psychosocial conditions with SBS complaints. It was recommended that the company improve the work environment by enhancing air circulation, maintaining workplace cleanliness, conducting regular environmental monitoring, and improving workers’ psychosocial conditions to reduce SBS complaints.